Variation in colour perception among normal individuals- A survey - V.S.S, Charan; M.P, Brundha; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
The Ishihara test consists of colored plates; it consists of a circle of dots appearing in different sizes and different colors. Within the pattern are dots that form a number or shape clearly visible to those with normal color vision and invisible, or difficult to see, to those with a red-green color vision defect. Other plates reveal numbers only to those with a red/green color deficiency and are invisible to those with normal red-green color vision, and a normal test consists of 38 plates. study is mainly intended to evaluate the colour perception among normal individuals This was mainly intended to determine the variation in color perception among normal individuals.